Programa de gestión escolar cooperativa para desarrollar competencias de planificación en dos instituciones educativas secundarias urbanas del distrito de Iquitos 2023 - Canayo Tamani, Zait Ibet (2025)
Findings are presented in relation to the study after the implementation of a cooperative school management program aimed at improving planning competencies, the following research question was formulated: What is the effect of the application of the cooperative school management program to develop planning competencies in two urban secondary educational institutions in the district of Iquitos 2023, It was also recommended that the main objective should be to: To determine the influence of the Cooperative School Management Program on the Development of Planning Competencies in two Urban Secondary Education Institutions in the District of Iquitos in the year 2023. The study is classified as applied research, with a single-group pre experimental design that includes pre-test and post-test. The population and sample consisted of 43 educators and principals. A specialist-validated instrument was applied, along with a survey and a performance test. The data and information that were collected from the application of a pretest and a posttest were evaluated, interpreted and discussed once the implementation process of the cooperative school management program was carried out. to the conclusion that the principals and teachers of the two educational institutions were able to develop their skills in institutional planning; With the use of these data, the hypothesis test was able to positively guide the consolidation of the current theoretical contribution, which in turn contributed to the resolution of the problems that were present in EI. Maynas and 60053 (Gen. E.P. Augusto Freyre García).